Enhancing the electrical, optical, and structure morphology using Pr2O3-ZnO nanocomposites: Towards electronic varistors and environmental photocatalytic activity - Saqib Rafique (Journal of Photochemistry and Photobiology A: Chemistry, 2021)
In this proposed research, the samples of undoped and several concentrations of praseodymium-doped zinc oxide (Pr2O3- ZnO) nanoparticles ranged from 0.001 g to 5 g were synthesized using a combustion technique as a simple, efficient, inexpensive, and environmental method. The structure, morphology, and chemical bonding were investigated by X-ray diffraction (XRD), and scanning electron microscopy (SEM), respectively, of the prepared Pr2O3-ZnO photocatalysts. The attained data from the previous devices sustained the ZnO growth from crystalline to satisfactory nanoparticle structure through changing the Pr3+-doping concentrations inside the host matrix. Furthermore, the optical features have been investigated via UV-Vis diffused reflectance spectroscopy (DR), and AC electrical conductivity was studied to investigate the Pr3+-nanoparticles' influence on the optical characteristics, energy bandgaps, of all proposed Pr2O3-ZnO nanostructured samples. The addition of Pr3+ dopants decreases the energy bandgap slightly and confines the photogenerated electron-hole recombination. The studied Pr2O3-ZnO nano-samples have been applied in photocatalytic degradation of methylene blue (MB) as an example for organic dyes and p-chlorophenol (p-CP) under visible light irradiation. The influence of Pr3+-concentration, H2O2 concentration, and pH of the medium on the photocatalytic reaction have been studied. As the praseodymium doping ratios increased; the photocatalytic efficiency increased. After the addition of moderate Pr3+-doping, further generation of hydroxyl radicals over ZnO. For 1% Pr3+-ZnO, the optimal photocatalyst is a degradation of 100% of p-chlorophenol and methylene blue solutions. The prepared Pr2O3-ZnO nanostructured samples are amazing, promising candidates in novel potential nano-applications for wide-ranged from varistors, wastewater treatments, biomedical and photocatalytic degradation for phenol and organic dyes to different environmental fields.